The Metaphorical Meaning of Natural Elements in Mandarin Idioms (chéngyǔ) - Ayesa Ayesa; Tri Wahyu Retno Ningsih (Universitas Negeri Semarang, 2026)
This study focuses on the analysis of the metaphorical meanings of vocabulary relating to the elements of nature in Mandarin Chinese. The natural elements used in this study are those recognised in the Five Elements theory (五行 Wŭ Xíng), which is a concept of great importance to Chinese society. These five elements comprise water (水 shuǐ), fire (火 huǒ), wood (木 mù), metal (金 jīn), and earth (土 tǔ). The data for this study consists of natural element vocabulary found in Mandarin Chinese idioms ( 成语 chéngyŭ), thereby enabling the identification of metaphorical meanings associated with these natural elements as constituent parts of the idioms. The idiom data was drawn from the Lancaster Corpus of Mandarin Chinese, focusing on the five idioms with the highest frequency. Using a qualitative research method, the data was analysed using conceptual metaphor theory. This study found an association between the meanings of the natural element vocabulary and the Five-Element theory. Furthermore, interpretations were found that align with the natural properties of these elements. The research was conducted to gain an understanding of the Chinese people’s way of thinking regarding the vocabulary of natural elements.